2016
DOI: 10.1016/j.jth.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Veloway 1: A natural experiment of new bicycle infrastructure in Brisbane, Australia

Abstract: Bicycle infrastructure is being constructed in Australia to encourage safer and faster cycling trips. However, there has been limited evaluation of the impact of infrastructure investments. This study examined the behavioural impact of a new segment of a dedicated bikeway (Veloway 1 [V1] Stage C) that links southern suburbs with Brisbane city centre. The V1 Stage C opened in June, 2013. Cyclists who used a pre-existing shared path that links southern suburbs with the city centre completed an intercept survey p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 32 publications
0
46
0
Order By: Relevance
“…Intercept surveys are brief surveys administered to cyclists at events or by stopping them while they are cycling. Recent work 41 suggests that combining Strava data with intercept survey data results in a more rigorous evaluation of the impact of infrastructure improvements on cycling behaviour than would the use of either data source alone. Intercept surveys are useful for capturing individual demographic and trip details (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Intercept surveys are brief surveys administered to cyclists at events or by stopping them while they are cycling. Recent work 41 suggests that combining Strava data with intercept survey data results in a more rigorous evaluation of the impact of infrastructure improvements on cycling behaviour than would the use of either data source alone. Intercept surveys are useful for capturing individual demographic and trip details (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…GPS-enabled mobile devices, such as smartphones, allow individuals to track and map their cycling routes [13,14,15,16]. More recently, crowdsourced cycling data are used to analyze cycling behavior [13,17] and make associations between cycling and health [9]. Strava is a popular website used to track users’ cycling and running activity via GPS-enabled devices, such as smart phones and smart watches.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, knowing where people like to cycle could help policymakers to improve cycling infrastructure more effectively (e.g., availability of cycle parking in areas of high demand) and promote road safety by giving priority to roads where there are more cycling trips. In several recent studies, Strava data has been used to map ridership over a city [13], evaluate the impact of bicycle infrastructure on cycling behavior [17], and investigate impacts of residential and employment density, land use diversity, cycling facilities and terrain on cycling behavior [9]. …”
Section: Introductionmentioning
confidence: 99%
“…To protect user privacy, Strava Metro anonymized and aggregated users' traces to streets of each city. Strava Metro data is of high potential in a wide range of applications, including mapping cycling activities over cities (Jesticoa et al, 2016), assessing effects of environmental factors on cycling behavior (Griffin and Jiao, 2015;Heesch et al, 2016) and assessing air pollution during cycling (Sun and Mobasheri, 2017). Moreover, by comparing cyclist counts between Strava data and manual count data in count stations, some studies have revealed that Strava Metro data is a good representation of cycling population (Jesticoa et al, 2016;Herrero, 2016).…”
Section: Introductionmentioning
confidence: 99%